Application of the “3-2-1” body surface localization method in intertrochanteric femoral fractures: a technical note - Wu, Xiaowei; Lin, Yanbin; Xu, Yangkai; Yan, Linglan; Tu, Shaochen (Frontiers in Surgery, 2024)
In femoral intertrochanteric fractures, poor incision positioning may result in inaccurate intramedullary nail placement direction, which increases the difficulty of reduction and thus the size and number of incisions. Repeated intraoperative fluoroscopy not only increases the radiation exposure of the surgeon but also affects the operative outcomes. This technical note proposes a method of identifying incision positioning preoperatively using the “3-2-1” body surface localization method. This auxiliary positioning technique uses a body surface locator and the lower limb force axis. It can predict the incisions for the needle insertion point, spiral blade, and locking nails, create minimally invasive incisions, avoid incorrect incision position, facilitate accurate intraoperative intramedullary nail placement, reduce the incision size, intraoperative bleeding, and radiation exposure, and improve surgical efficiency and reduction quality.